METHODOLOGY OF EDUCATING THE INTEREST AND PHYSICAL QUALITIES OF GENERAL SECONDARY SCHOOL STUDENTS IN THE SPORT OF BASKETBALL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Methodical approaches to interest the students of the general secondary school in the sport of basketball and to educate their physical qualities are considered in this article. The article describes approaches based on special educational activities and game elements to form a healthy lifestyle among schoolchildren, to develop their physical qualities (speed, strength, agility, endurance and balance) by involving them in sports activities. offers. At the same time, recommendations are given on the use of pedagogical technologies, interactive methods and motivational approaches in the organization of basketball training.